PENGARUH MORALITAS INDIVIDU DAN KOMPETENSI APARATUR TERHADAP PENCEGAHAN FRAUD PENGELOLAAN KEUANGAN DESA DI KABUPATEN MINAHASA - Mawikere, Lidia Marlina; Morasa, Jenny; Kapojos, Peter (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to (1) determine the influence of individual morality on the prevention of village financial fraud (2) determine the influence of apparatus competence on the prevention of village financial fraud. The type of research is quantitative research. The population in this study consisted of the village head, village secretary, village treasurer and Village Consultative Body totaling 40 people. The data collection technique used the questionnaire method. The data analysis technique used multiple linear regression. The results of the study showed (1) individual morality had an effect on the prevention of village financial fraud (2) apparatus competence had an effect on the prevention of village financial fraud (3) individual morality and apparatus competence had a simultaneous effect on the prevention of village financial fraud